Opredelitev oseb javnega prava po pravilih javnega naročanja - Kirn, Marko (Podjetje in delo, 2016)
The article sets the analytical tool for assessing the status of legal entities under the rules of public procurement, when these entities are not organized in the legal form, typical for bodies governed by the public law. The key is to assess whether in a concrete case the circumstances are present which show that such an entity meets the needs of the general interest, not having an industrial or commercial nature. What are these circumstances in general can be induced from the case-law of the ECJ. The author analyzes this case-law in detail. The case-law established under the earlier directives on public procurement (Directive 2004/18/EC, Directive 93/37/EEC and Directive 92/50/EEC) continues to be relevant, as Directive 2014/24/EU, compared with earlier directives on public procurement, brought no changes concerning the definition of bodies governed by the public law. The national act on public procurement (ZJN-3) did not codify completely the existing case-law on the definition of bodies governed by the public law.
Keywords: javna naročila; javni interes; javno pravo; sodišča; sodna praksa